Criteria of metrical transitivity of Gaussian homogeneous functions - Tempelman, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Темпельман. Критерии метрической транзитивности гауссовских однородных случайных функций A. Tempelmanas. Gauso homogeninių atsitiktinių funkcijų metrinio tranzityvumo kriterijai